O mundo secreto das abelhas: produção de material didático à luz dos fundamentos da Educação ambiental crítico-transformadora via temas geradores - Spiazzi, Paula Santos (Universidade Federal de São Carlos, 2022)
The legacy of a critical-transformative education is one of the main legacies of the work and work of Paulo Freire, which is based on problematization, contextualization and interdisciplinarity in order to train critical-transformative citizens, so that the practices and knowledge seized by the students allow them to act in reality in a way that relationships between nature, society and culture. This conception freirean education articulated to critical environmental education (EAC), configures the Critical-transforming environmental education (EACT) via generating themes. This research was developed with a class of elementary school II, seeking the survey of sociocultural and natural contradictions around environmental issues, in search of the theme adopted as a criterion for the elaboration of an EACT programming. Essa resultou na produção de um material didático de EAC voltado ao papel das abelhas no meio ambiente, compreendido em sua totalidade, bem como na relação entre os seres humanos e as abelhas, visando colaborar com a formação de sujeitos críticos para uma atuação transformadora, empoderadora e humana, na realidade concreta injusta, exploratória e desigual.
El mundo secreto de las abejas: producción de material didáctico a la luz de los fundamentos de la educación ambiental transformadora crítica a través de la generación de temas
The secret world of bees: production of didactic material in the light of the fundamentals of critical-transforming environmental education via generating themes
Keywords: Pesquisa-ação; Educação libertadora; Sustentabilidade; Educação crítica; Formação humana; Action search; Liberating education; Sustainability; Critical education; Human formation; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO